ответ: S≈0,33 кв. ед.
Пошаговое объяснение:
y=x²-6x+9 y=0 x=2
y=x²-6x+9 =(x-3)²=0
x-3=0
x=3
S=₂∫³(x²-6x+9-0)dx=(x³/3)-3x²+9x ₂|³=(3³/3)-3*3²+9*3-((2³/3)-3*2²+9*2)=
=9-27+27-((8/3)-12+18)=9-(2²/₃+6)=9-8²/₃=1/3.
у =1
у=2^2-6*2+9 (наверное эту 2 надо умножить, по моему.).вычислить степень.
у=4 - 12 + 9 = 1
ответ: S≈0,33 кв. ед.
Пошаговое объяснение:
y=x²-6x+9 y=0 x=2
y=x²-6x+9 =(x-3)²=0
x-3=0
x=3
S=₂∫³(x²-6x+9-0)dx=(x³/3)-3x²+9x ₂|³=(3³/3)-3*3²+9*3-((2³/3)-3*2²+9*2)=
=9-27+27-((8/3)-12+18)=9-(2²/₃+6)=9-8²/₃=1/3.
у =1
Пошаговое объяснение:
у=2^2-6*2+9 (наверное эту 2 надо умножить, по моему.).вычислить степень.
у=4 - 12 + 9 = 1